EVALUASI PELAKSANAAN PROGRAM RASKIN DI KECAMATAN BALAESANG KABUPATEN DONGGALA - Isman, Isman (Katalogis, 2016)
This research aimed to realizing program of distribution Raskin and obstacle factor on the poor at Balaesang District of Donggala Regency. This research using descriptive qualitative method by using table distribution of frequency. The research sampling are 101 family as a responden from representation each subdistrict at Balaesang. The results of this study indicate that distribution of Raskin wasn't yet maximum accomplished. By the six indicators set, only three accomplished namely: (1) timely indicator, (2) indicator of administration requirements and (3) indicators of the quality of rice. The obstacle factor the implementation of the program is on: (1) target indicators, (2) timely indicators and (3) the indicators sufficiency. The cause not on time because the only BPS data was used without verification through village official consultation, not timely due to the delay in the distribution of Raskin still three days or a week or more, not just the right amount because it is still the discovery of some public recognition Raskin recipients who felt less in adequate. The supporting factors of implementing the Raskin program namely community support and attention of government in carrying out their duties, public enthusiasm in response the program and good coordination between the implementing institution of the program.